The Paradox of Social Capital: Reflections on Disaster Response and Climate Adaptation - Embornas, Amabelle (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2020)
Social capital refers to social ties, norms, and networks that facilitate group or individual access to resources. Social capital has a collective dimension, and its benefits are generally shared by members of a community. While social capital is generally recognized as an important means to building community resilience, it takes on a double-edge character when applied to real situations. Based on literature review, this paper elaborates how social capital plays its dual role in the process of adapting to climate change towards making communities resilient. Social capital simultaneously strengthens the ability of the community to survive a disaster and recover, while being a barrier to democratic principles and policies.